SAXS study of gelation, aging and drying of silica-polypropyleneglycol hybrid materials - Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Chaker, J. A.; Pulcinelli, Sandra Helena [UNESP]; Craievich, A. F. (Japan J Applied Physics, 1999)
New silica-polypropyleneglycol ormosils (organically modified silicates) with covalent bends between the organic (polymer) and inorganic (silica) phases have been prepared by the sol-gel process. Their structural evolution during sol formation, sol-gel transition, gel aging and drying has been studied in situ by small-angle X-ray scattering (SAXS). The experimental SAXS curves corresponding to sols and gels exhibit features expected from fractal objects. Clusters of size around 55 Angstrom with an initial fractal dimension D = 2.4 are formed in the sol. They are constituted of small primary silica particles chemically crosslinked at the end of the polymer chains. A strong liquid-like spatial correlation between the silica particles develops during drying due to the shrinkage of the polymeric network induced by water and ethanol evaporation. The continuous increase in SAXS intensity during drying, while the interparticle distance remains constant, is a consequence of the progressive growth of the dry fraction of the total volume. After drying, the gel structure consists of a rather compact arrangement of silica particles embedded in the polypropyleneglycol matrix.
Keywords: SAXS; sol-gel process; ormosils